The Preparation, Antioxidant Activity Evaluation, and Iron-Deficient Anemic Improvement of Oat (Avena sativa L.) Peptides–Ferrous Chelate - Yuanqing, He; Pengyao, Yang; Yangyang, Ding; Min, Chen; Rui, Guo; Yuqing, Duan; Haihui, Zhang; Haile, Ma (Frontiers in Nutrition, 2021)
Iron chelating peptides have been widely considered as one of the best iron supplements to alleviate iron deficiency. In this study, a novel oat peptides-ferrous chelate (OP-Fe2+) was prepared from the antioxidant oat peptides obtained in our laboratory. The optimal preparation condition was obtained through the single-factor and response surface methodology (RSM), and the chelating rate could reach 62.6%. After chelation, the OP-Fe2+ exhibited a significantly higher 2, 2-diphenyl -1-picrylhydrazyl (DPPH) radical scavenging activity than oat peptides. It was discovered that the hemoglobin concentration and the number of red blood cell (RBC) level in OP-Fe2+-treated iron-deficient anaemic (IDA) rats were significantly higher than untreated IDA rats. The OP-Fe2+ could also improve the hypertrophy of spleen, the serum iron (SI) , the total iron and binding capacity (TIBC) and serum ferritin (SF) level in IDA rats. In addition, the OP-Fe2+ treatment significantly increased the antioxidant activities of super oxidase (SOD) and glutathione (GSH) in the liver homogenate of IDA rats. Therefore, the OP-Fe2+ is an effective type of iron supplement for IDA rats, which could be a promising source with anti-anaemia and antioxidant activity.